Cessation of daily wheel running differentially alters fat oxidation capacity in liver, muscle, and adipose tissue. - Laye, M; Rector, R; Borengasser, S; Naples, S; Uptergrove, G; Ibdah, J; Booth, F; Thyfault, J (2009)
Physical inactivity is associated with the increased risk of developing chronic metabolic diseases. To understand early alterations caused by physical inactivity, we utilize an animal model in which rats are transitioned from daily voluntary wheel running to a sedentary condition. In the hours and days following this transition, adipose tissue mass rapidly increases, due in part to increased lipogenesis. However, whether a concurrent decrease in fatty acid oxidative capacity (FAO) in skeletal muscle, liver, and adipose tissue occurs during this period is unknown. Following 6 wk of access to voluntary running wheels (average distance of approximately 6 km a night), rats were rapidly transitioned to a sedentary state by locking the wheels for 5 h (WL5) or 173 h (WL173). Complete ([(14)C]palmitate oxidation to (14)CO(2)) and incomplete ([(14)C]palmitate oxidation to (14)C-labeled acid soluble metabolites) was determined in isolated mitochondrial and whole homogenate preparations from skeletal muscle and liver and in isolated adipocytes. Strikingly, the elevated complete FAO in the red gastrocnemius at WL5 fell to that of rats that never ran (SED) by WL173. In contrast, hepatic FAO was elevated at WL173 above both WL5 and SED groups, while in isolated adipocytes, FAO remained higher in both running groups (WL5 and WL173) compared with the SED group. The alterations in muscle and liver fat oxidation were associated with changes in carnitine palmitoyl transferase-1 activity and inhibition, but not significant changes in other mitochondrial enzyme activities. In addition, peroxisome proliferator-activated receptor coactivator-1alpha mRNA levels that were higher in both skeletal muscle and liver at WL5 fell to SED levels at WL173. This study is the first to demonstrate that the transition from high to low daily physical activity causes rapid, tissue-specific changes in FAO.